Getting started with deep learning - Patterson, Josh (Consultant); Gibson, Adam, 1989- (O'Reilly, 2018)
Although interest in machine learning has reached a high point, lofty expectations often scuttle projects before they get very far. How can machine learning--especially deep neural networks--make a real difference in your organization? This lesson provides a practical overview of the foundations of neural networks and deep learning and also looks at deep networks. This lesson is for you because you are a data scientist or software developer who wants to understand and be able to use efficient tools to implement programs capable of learning from data.